1990
DOI: 10.1002/jnr.490260212
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐dependent peroxidation of rat brain: A regional study

Abstract: Iron has been shown to initiate a variety of free radical reactions in biological systems. The present study examined the in vitro susceptibility of homogenates prepared from different regions of rat brain to iron-induced peroxidation. Among the regions studied, basal thiobarbituric acid-reactive product (TBAR) formation is highest in the cerebellum and amygdala, intermediate in the cortex, hippocampus, and neostratium, and lowest in the hypothalamus, midbrain, and brainstem. In the presence of 200 microM FeCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…It is likely that these results mainly represent the artifactual basal values of TBARS generated during the assay previously reported by several researchers (Gutteridge and Halliwell, 1990;Götz et al, 1993;Li and Chow, 1994). However, the concentrations of these basal values were significantly lower than those obtained in a previous study in supernatant cerebellum fractions (Subbarao and Richardson, 1990). The reason for such a discrepancy appears to be methodological.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It is likely that these results mainly represent the artifactual basal values of TBARS generated during the assay previously reported by several researchers (Gutteridge and Halliwell, 1990;Götz et al, 1993;Li and Chow, 1994). However, the concentrations of these basal values were significantly lower than those obtained in a previous study in supernatant cerebellum fractions (Subbarao and Richardson, 1990). The reason for such a discrepancy appears to be methodological.…”
Section: Discussioncontrasting
confidence: 53%
“…Tissue homogenates were prepared on ice using a teflon pestle (10-12 strokes) and centrifuged at 3000 × g for 15 min. The supernatant that contained microsomes, mitochondria and synaptosomes (Subbarao and Richardson, 1990) was retrieved. From this supernatant, 20 l was taken to determine the amount of proteins using Lowry's assay (1951).…”
Section: Assay Of Lipid Peroxides and Protein Estimation On Cerebellamentioning
confidence: 99%
“…Remarkably, in the present study, a markedly reduced numbers of Apx isozyme found in the brain tissues of aged untreated rats suggests that the brain tissue may be particularly susceptible to oxidative stress. A possible reason for this could be that since the brain is rich in non-heme iron, it could be catalytically involved in the production of oxygen free-radicals (Subbarao & Richardson, 1990). Another possible explanation is that the presence of unsaturated fatty acids in high concentrations makes the brain tissue good substrates for the occurrence of peroxidation reactions (Ogawa, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of iron accumulation is mediated by the formation of reactive species, including hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (•OH) [15,16]. Both •OH and the products of •OH can react with polyunsaturated fatty acids in cell membranes, increase rates of peroxidation in the brain and contribute to neuronal damage [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…An injection of iron in the brain of animal models is associated with oxidative injury, neurodegeneration and neuron death [9][10][11][12][13][14]. The effect of iron accumulation is mediated by the formation of reactive species, including hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (•OH) [15,16].…”
Section: Introductionmentioning
confidence: 99%